Relation of Follicular Fluid Soluble Receptor for Advanced Glycation End-Products Concentration and Anti Mullerian Hormone in Polycystic Ovary Syndrome and Non-PCOS Women Referring to In Vitro Fertilization Center: Case-Control Study - Neda Emami; Ashraf Moini; Samira Vesali (International Journal of Fertility and Sterility)
Background: Reproductive dysfunctions of polycystic ovary syndrome (PCOS) and blood anti-mullerian hormone(AMH) concentration are significantly influenced by the dietary advanced glycation end products (AGEs). The interplaybetween AGEs and their soluble form of receptor, might exert a protective role on the follicular environment andaffect AMH concentration. This study investigated the relationship between soluble receptor for advanced glycationend-products (sRAGE) levels in follicular fluid (FF) and serum AMH levels in PCOS and non-PCOS women.Materials and Methods: Among 43 women of reproductive age who participated in this case-control study 26 non-PCOS women were assigned to the control group, while 17 participants were diagnosed with PCOS and allocatedto the case group. Prior to the in vitro fertilization (IVF) procedure, fluid samples were collected and levels of FFsRAGEs and serum AMH were recorded through the use of commercially available ELISA kits.Results: Correlation analysis, without age adjusting, revealed a statistically considerable and positive associationbetween FF sRAGE and serum AMH concentration in PCOS women (P=0.012, r=0.596). Moreover, after age stratification,the same pattern was observed in some age groups; in PCOS women aged 40 years or older (r=1, P<0.001), aswell as those younger than 30 years (r=0.922, P=0.003), correlation analysis demonstrated a significant and positiverelationship between FF sRAGE and serum AMH levels.Conclusion: The association between sRAGE and AMH in women with PCOS is primarily affected by their age,whereas non-PCOS women showed no relationship. The results show that the levels of these receptors (sRAGE)show their specific effects in young women and women over 40 years old and not in middle age and target the ovarianreserve. It seems to act as a defensive shield in older women and increase fertility in young women.